Vormärz und Aufklärung - Eke, Norbert Otto (Vormärz-Handbuch)

Exil - Eke, Norbert Otto (Vormärz-Handbuch)

Habitueller Antiklassizismus. Christian Dietrich Grabbe und die Kritik an Klassik und Romantik im Vormärz - Eke, Norbert Otto (Zwischen Emanzipation und Sozialdisziplinierung: Pädagogik im Vormärz)

Nachruf: Hartmut Steinecke zum Gedenken - Eke, Norbert Otto (Zeitschrift für deutsche Philologie)

Der ‚Eigene Kalender‘ des Erinnerns: Die Wahrheit der erfundenen Erinnerung in Herta Müllers Romanen, Erzählungen und Essays - Eke, Norbert Otto (German Life and Letters (Special Issue: Herta Müller and the Currents of European History))

Auslegungsmethode für zyklisch beanspruchte Stahl/CFK-Klebverbindungen unter besonderer Berücksichtigung des Rissfortschritts - Kowatz, Jannik; Teutenberg, Dominik; Meschut, Gerson (20. Kolloquium Gemeinsame Forschung in der Klebtechnik)

CFD-basierte Untersuchung von Zweiphasenströmungen in strukturierten Packungen - Bertling, René; Hack, Mathias; Ausner, Ilja; Kenig, Eugeny

CFD-Simulationen von Film- und Rinnsalströmungen auf mikrostrukturierten Oberflächen - Bertling, René; Hack, Mathias; Ausner, Ilja; Kenig, Eugeny

Dynamische Simulation von industriellen Kreislaufprozessen zur Vermeidung von Notfallsituationen bei der chemischen Absorption - Bothe, Mike; Fedorov, A.; Frei, H.; Lutters, N.; Kenig, E. Y. (Chemie Ingenieur Technik)

Semi-automatized consistency assessment in Scenario-Technique: Generic consistency patterns and user types - Gräßler, Iris; Scholle, Philipp; Thiele, Henrik (ISPIM Conference Proceedings)

Automatisierte Identifikation und Charakterisierung von Anforderungsabhängigkeiten – Literaturstudie zum Vergleich von Lösungsansätzen - Gräßler, Iris; Preuß, Daniel; Oleff, Christian (Proceedings of the 31st Symposium Design for X (DFX2020); 16. - 18. Sep. 2020)

Which future do we want? It's up to us! - 4 future scenarios for automation 2030 - Gräßler, Iris; Bettenhausen, Kurt D.; Bilgic, Attila M.; Dirzus, Dagmar (at-Automatisierungstechnik 68(6))

The new V-Model of 2206 and its validation - Gräßler, Iris; Hentze, Julian (at-Automatisierungstechnik 68(5))

Scenario Technique - Gräßler, Iris; Scholle, Philipp; Thiele, Henrik (Integrated Design Engineering. Interdisciplinary and Holistic Product Development)

7. Workshop Mensch-Maschine-Interaktion in sicherheitskritischen Systemen - Mentler, Tilo; Reuter, Christian; Nestler, Simon; Kaufhold, Marc-Andre; Herczeg, Michael; Pottebaum, Jens (Mensch und Computer 2020 - Workshopband)

Method for Systematic Assessment of Requirement Change Risk in Industrial Practice - Gräßler, Iris; Oleff, Christian; Scholle, Philipp (Applied Sciences 23/2020 (23))

Automation 2030. Zukunft gestalten - Szenarien und Empfehlungen - Gräßler, Iris; Thiele, Henrik; al., et.

Digitaler Zwilling - WiGeP Positionspapier - Stark, Rainer; Thoben, Klaus-Dieter; Gerhard, Detlef; Hick, Hannes; Kirchner, Eckhard; Anderl, Reiner; Wartzack, Sandro; Krause, Frank-Lothar; Gräßler, Iris; Pottebaum, Jens; Schleich, Benjamin; Stelzer, Ralph; et al.

GIWAXS-SIIRkit: scattering intensity, indexing and refraction calculation toolkit for grazing-incidence wide-angle X-ray scattering of organic materials - Savikhin, Victoria; Steinrück, Hans-Georg; Liang, Ru-Ze; Collins, Brian A.; Oosterhout, Stefan D.; Beaujuge, Pierre M.; Toney, Michael F. (Journal of Applied Crystallography)
Grazing-incidence wide-angle X-ray scattering (GIWAXS) has become an increasingly popular technique for quantitative structural characterization and comparison of thin films. For this purpose, accurate intensity normalization and peak position determination are crucial. At present, few tools exist to estimate the uncertainties of these measurements. Here, a simulation package is introduced called GIWAXS-SIIRkit , where SIIR stands for scattering intensity, indexing and refraction. The package contains several tools that are freely available for download and can be executed in MATLAB. The package includes three functionalities: estimation of the relative scattering intensity and the corresponding uncertainty based on experimental setup and sample dimensions; extraction and indexing of peak positions to approximate the crystal structure of organic materials starting from calibrated GIWAXS patterns; and analysis of the effects of refraction on peak positions. Each tool is based on a graphical user interface and designed to have a short learning curve. A user guide is provided with detailed usage instruction, tips for adding functionality and customization, and exemplary files.

Crystallization and Organic Field‐Effect Transistor Performance of a Hydrogen‐Bonded Quaterthiophene - Gebers, Jan; Özen, Bilal; Hartmann, Lucia; Schaer, Michel; Suàrez, Stéphane; Bugnon, Philippe; Scopelliti, Rosario; Steinrück, Hans-Georg; Konovalov, Oleg; Magerl, Andreas; Brinkmann, Martin; Petraglia, Riccardo; et al. (Chemistry – A European Journal)